Leptobacillium cavernicola, a newly discovered fungal species isolated from several Paleolithic-decorated caves in France - Leplat, Johann; Francois, Alexandre; Bousta, Faisl (Phytotaxa, 2022)
Several interesting fungal strains were recovered from air and surface samplings in a number of Paleolithic-decorated caves in France during multiple surveys. Multi-locus (ITS, LSU, SSU, RPB1, RPB2 and TEF-1α) phylogenetic analysis of these strains through maximum likelihood and Bayesian inference coupled with a morphological characterization revealed a new fungal taxa, Leptobacillium cavernicola sp. nov. This new species morphologically and phylogenetically close to Leptobacillium muralicoa, which was also first isolated from a cultural heritage context. The study of this new species led us to reconsider the taxonomic position of strains that have hitherto been identified as Leptobacillium spp., suggesting that several new species could be added to the genus.